Between ecological orientation of water protection and commercialisation of water management: new requirements for spatial planning and regional policy - Moss, Timothy (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
The paper analyses two parallel, but distinct, trends of water management in Germany — the ecological orientation of water protection and the commercialisation of water services — in terms of their relevance for spatial development. It describes the principal features of each of these trends, illustrates their spatial dimensions and elucidates their implications for spatial planning and regional development strategies. Conclusions are drawn on how spatial planning and regional policy could be used to greater effect to shape these ongoing — and thus still open — processes of ecological orientation and commercialisation in the water sector.
Keywords: Water Framework Directive; Water protection; Water services; Spatial planning